Launching ILRI open access week workshop 2019: Jimmy Smith - Smith, Jimmy W. (International Livestock Research Institute, 2019)
Jimmy Smith, ILRI director general, launching the ILRI open access week 2019. ILRI celebrated Open Access Week on 23-25 October with a number of activities to promote and build awareness on how open access can support research. This is a recording from WebEx so the picture quality is not high; but what he says is clear and important for getting ILRI's research into use.